Studies on water mites (Acari, Hydrachnidia) from the Himalayas, I. The water mite genus Feltria Koenike, with descriptions of eight new species - Pesic, Vladimir; Panesar, Arne (Zootaxa, 2008)
New information about the distribution of species of the water mite genus Feltria Koenike (Acari: Hydrachnidia, Feltriidae) in the Indian Himalayas is presented. Eight species (Feltria indica, F. tuzovskyi, F. schwoerbeli, F. himachali, F. kulluis, F. balneatoris, F. sannae and F. gereckei) are described as new to science; F. rubra Piersig, 1898 and F. longipalpis (Lundblad, 1941) are new to the Indian water mite fauna and for the latter species the first description of the female is provided.